Evidence for rapid divergence of sensory systems between Texas populations of the Mexican tetra (Astyanax mexicanus) - Enriquez, Maya S.; Swanson, Nathan; Putland, Rosalyn L.; Tait, Ti; Gluesenkamp, Andrew G.; McGaugh, Suzanne E.; Mensinger, Allen F. (Frontiers in Ecology and Evolution, 2023)
Population divergence is often quantified using phenotypic variation. However, because sensory abilities are more difficult to discern, we have little information on plasticity and rate of sensory change between different environments. The Mexican tetra (Astyanax mexicanus) is a fish distributed throughout Southern Texas and Northern Mexico and has evolved troglomorphic phenotypes, such as vestigial eyes and reduced pigmentation, when surface ancestors invaded caves in the past several hundred thousand years. In the early 1900s, surface A. mexicanus were introduced to the karstic Edwards-Trinity Aquifer in Texas. Subsequent cave colonization of subterranean environments resulted in fish with phenotypic and behavioral divergence from their surface counterparts, allowing examination of how new environments lead to sensory changes. We hypothesized that recently introduced cave populations would be more sensitive to light and sound when compared to their surface counterparts. We quantified divergence using auditory evoked potentials (AEPs) and particle acceleration levels (PALs) to measure differences in sound sensitivity, and electroretinography (ERGs) to measure light sensitivity. We also compared these results to measurements taken from native populations and lab-born individuals of the introduced populations. Honey Creek Cave fish were significantly more sensitive than proximate Honey Creek surface fish to sound pressure levels between 0.6 – 0.8 kHz and particle acceleration levels between 0.4 – 0.8 kHz. Pairwise differences were found between San Antonio Zoo surface and the facultative subterranean San Pedro Springs and Blue Hole populations, which exhibited more sensitivity to particle acceleration levels between 0.5 – 0.7 kHz. Electroretinography results indicate no significant differences between populations, although Honey Creek Cave fish may be trending towards reduced visual sensitivity. Auditory thresholds between wild-caught and lab-raised populations of recently invaded fish show significant differences in sensitivity, suggesting that these traits are plastic. Collectively, while these results may point to the rapid divergence of A. mexicanus in cave habitats, it also highlights the responsive plasticity of A. mexicanus auditory system to disparate environments.